The Unexpected Impact of Prosperity: How the Manipulation of the Consequences of Globalization by the Far-Right Movements Endanger the International Order? - Matelly, Sylvie (CEBRI-Revista: Brazilian Journal of International Affairs, 2024)
At the Cold War’s end, liberal globalization was seen as the “end of history,” bringing peace and prosperity, which didn’t happen. By the 1990s, NGOs, civil society, and researchers highlighted winners and losers. Far-right movements exploited this, threatening democracies and global order, without solutions for the marginalized.